2022
DOI: 10.7759/cureus.22376
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Epidemiological Study of Neurofibromatosis Type 1 and Its Relation to Quality of Life: A Cross-Sectional Study From India

Abstract: Introduction: Neurofibromatosis type 1 (NF1) is an inherited neuroectodermal abnormality with multisystem effects, which can have heavy psychological and physical burdens, especially in countries like India, wherein skin disease is significantly stigmatized. This study was performed to understand the clinical and epidemiological trends of NF1 at a tertiary care center in India and evaluate the association between clinical severity and quality of life in these patients.Methods: We conducted a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Although the health risks posed by NF1 are not often serious, NF1 considerably affects the patient’s quality of life as it causes visible changes in their appearance and leads to social stigma (Bicudo et al, 2016; Mahajan et al, 2022). Thus, NF1 patients are less satisfied with their lives and have more mental health issues, pain (Cannon et al, 2018), and inferior self-reported body image (Granström et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the health risks posed by NF1 are not often serious, NF1 considerably affects the patient’s quality of life as it causes visible changes in their appearance and leads to social stigma (Bicudo et al, 2016; Mahajan et al, 2022). Thus, NF1 patients are less satisfied with their lives and have more mental health issues, pain (Cannon et al, 2018), and inferior self-reported body image (Granström et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the effects of NF1 on various aspects of quality of life (QoL) is important to implement beneficial strategies to improve the QoL of NF1 patients. Researches have used several questionnaires to study the QoL of NF1 patients primarily by post, mail or online surveys (SF-36, Skindex-29, NF1-AdQoL, WHOQOL-100, WHOQOL-Bref, cNF-Skindex, EQ-5D-5 L, INF1-QOL, PedsQL, DLQI, BoN, CHQ-PF50, ITQOL… ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In those studies, the QoL of individuals with NF1 was systematically below the QoL of the general population.…”
Section: Introductionmentioning
confidence: 99%